A residência multiprofissional no Hospital São Paulo (HU – Unifesp): percepção dos residentes sobre o processo de ensino em saúde e atuação em equipe interprofissional - Degiovani, Mariella Vargas [UNIFESP] (2017)
Introduction: Multiprofessional residencies in the health field exist in Brazil merging as one of the strategies employed to increase the process of hands-on learning, seeking the consolidation of the propositions of the SUS (Brazilian Public Health System). As such, the multiprofessional residency programs have inserted themselves in many scenarios, from hospital-based to primary care, when they were implemented in the Family Health Strategy. However, despite its broad reach, there are few initiatives seeking to understand, know and evaluate said residencies and their impact in the shaping of health professionals. Objectives: This research sought to analyze the perception of multiprofessional residents regarding conceptions and experiences of interprofessional work within Multiprofessional Residencies in Health in HSP-UNIFESP. Methodology: This project consisted in a qualitative research, of descriptive-exploratory character. The data was collected through semi-structured interviews. The analyzed population were the first and second year residents of the Multiprofessional Health Residency program of the HSP-UNIFESP. Interviews were recorded and transcripted and data was analyzed through the content analysis technique, thematic modality. Results: A total of 17 multiprofessional residents were interviewed. Thematic categories relevant to this study were: motivation for the insertion in the Multiprofessional Health Residency program, conception of teamwork in the Multiprofessional Health Residency program and contribution of the Multiprofessional Health Residency program to working in a multiprofessional team. The perceptions captured by this study point towards a certain heterogeneity among the experiences of residents. The motivations that led to seeking a Multiprofessional Health Residency program were, for the most part, pragmatic and aimed towards the obtention of a complementary formation after completing a degree. Even though many subjects had previous knowledge of the concept of work in a multiprofessional team, the experience was new to all and pointed as a significant gain regarding Multiprofessional practice. Subjects pointed out, however, that there were expressive difficulties in the conduction of said work, notably a dichotomy between the elaborated pedagogical project and the one that was implemented, showing a break of expectations in the formation process. Furthermore, many participants highlighted the part that the Multiprofessional Health Residency program played as a catalyzer in a self-knowledge process. Conclusion: The study represents a deepening on the teaching activities within the Multiprofessional Health Residencies. The analyzed categories represent essential points towards perfecting the formation process of residents in the multiprofessional health field and also the need of an approximation between the formulated pedagogical project and the teaching practices. Specific actions in integration between teaching and practice can improve the evaluation of Multiprofessional Health Residency programs through teaching strategies. Among those strategies is the creation of an interprofessional group meant to rethink practices in the Multiprofessional Health Residency program, as well as other studies that can address the professor and preceptor perspectives in Multiprofessional Health Residency programs in order to complement the information obtained in the study.